Hubungan Peran Teman Sebaya Dan Penggunaan Media Sosial Terhadap Pola Makan Remaja - Apriliani, Arni; Fitriani, Rosmauli Jerimia (Poltekkes Kemenkes Jambi, 2024)
Background: Adolescence is a change from childhood to adulthood. This causes problems, namely being overweight (obesity), underweight and wrong eating patterns. Nowadays, teenagers consume a lot of food advertised on social media, but these foods do not contain strong enough nutrients. Apart from that, the influence of the social environment, such as peers, plays an important role in unhealthy eating patterns. The aim of this research is to analyze the relationship between the role of peers and the use of social media on the eating patterns of adolescents at PGRI Kasihan Bantul Middle School in 2024. The research method uses observational research with a cross-sectional research design. Sampling used a simple random sampling technique. Results: Based on the research results, it was found that there was a relationship between the role of peers on eating patterns and a value of p= 0.031, and there was no relationship between the use of social media and the eating patterns of teenagers at PGRI Kasihan Bantul Middle School with a value of p= 0.096. Conclusion: There is a relationship between the role of peers on teenagers' eating patterns and there is no relationship between the use of social media on teenagers' eating patterns at PGRI Kasihan Bantul Middle School.